PEMANFAATAN VIRTUAL BOX DALAM PRAKTIKUM ADMINISTRASI SERVER MENGGUNAKAN TEKNIK DHCP PADA MIKROTIK ROUTER OS - Fati Gratianus Nafiri Larosa (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2016)
Today, Server Administration is very important to optimize some services given by Server to all users. DHCP (Dynamic Host Control Protocol) is one of the services provided by Server. In this paper, DHCP is configured on Mikrotik RouterOS 5.25 as a Router to keep Clients connected in Network. Beside, DNS was configured both in Microsoft Linux Fedora 12 and Windows Server 2008. The client machines using Microsoft Windows XP that were installed on Virtual Environment provided by Oracle VM Virtual Box, connected (got IP Addresses) automatically.